(3GdGSJKeGQ aj GdJQNjU GdGeJjGRj (B:s ((3GdaQGfTGjR(B) = Investment In The Franchise License /s - (3MHjH, eUWai SdeGfs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2011)
(3YfhGf gPG GdcJGH gh (B((3GdGSJKeGQ aj GdJQNjU GdGeJjGRj GdaQGfTGjR(B) (3GdPj gh ehVhY MOjK GdYUQ aj eLGd JWhQ GdGbJUGO GdYGdej GdPj jTgOg GdYGde aj gPg GdMbHI ef GdJGQjN, hdbO GNJGQ GdeDda gPG GdYfhGf HOdG ef GdJQLeI GdMQajI dcdeI aQGfTGjR (B(Franchise) (3hGdJj JWdb YdjgG efXeI GdhjHh (B(WIPO) (3GSe GdJQNjU GdJYGbOj GdPj dG jSHZ Gdeaghe GdUMjM deYfi GdcdeI, MjK Ef LejY GdJQGNjU GdJLGQjI gj JQGNjU JYGbOjI(B. (3hdbO HOCJ GdTQcGJ GdYGdejI JUOQ efJhLGJgG hJbOe NOeGJgG HWQjbI LOjOI, HYO GfJgGA GdMQH GdYGdejI GdKGfjI Yf WQjb JQNjUGJ JNJda aj WHjYJgG Yf GdJQGNjU GdGYJjGOjI, EP TedJ fbd hJMhjd UfGYI GdJcfhdhLjG, hJNhaG Yf bQUfI GdeYQaI hGdeYdheGJ GdJj bO jfWhj YdjgG Pdc GdGfJbGd, abO fTCJ YdGbI YVhjI eY bhGfjf GdedcjI GdacQjI, hGdJj JHdhQJ Ydi Tcd eYGgOGJ JOjQgG GdhjHh (B(WIPO)(3, hJdRe gPg GdeYGgOGJ GdOhd GdCYVGA HGdONhd aj eTGhQGJ ajeG HjfgG HfGA Ydi WdH Cj efgG, EPG cGf ehGWf CMO GdCYVGA eJgeG HGdTQhY aj eeGQSGJ efGajI ddefGaSI GdeTQhYI aj GdCQGVj GdNGVYI dhdGjI YVh BNQ(B. (3hJQi GdCShGb GdYQHjI ZRhG YfjaG ef bHd GdTQcGJ GdYGdejI GdeJNUUI aj gPG GdbWGY ef GdGbJUGO, hdG YLH aj Pdc aGdefWbI GdYQHjI JaJbQ Edi GdUfGYGJ GdJcfhdhLjI GdJj GJUaJ HgG Ohd fehQ TQb BSjG, hHfaS GdhbJ aEfgG JTcd ShbG GSJgdGcjI egeI(B. (3hef gPG GdUYjO hef WHjYI GdJQNjU GdGeJjGRj (B((3GdJj JJWdH WQaG jeKd GdeQNU dg(B)(3, abO Cda GdeDda gPG GdcJGH GdPj jTQM GdfhGMj GdbGfhfjI hGdYedjI aj YTQI aUhd, SJI aUhd efgG JWQM GdfhGMj GdbGfhfjI hJYGdL GdaUhd GdCNQi GdfhGMj GdYedjI cGdGSJTGQGJ GdegfjI hGdJehjd hGdeMGSHI hGdbhGYO hWQb Jbjje GdLgGR GdGeJjGRj(B.s
(3JUeje hEfJGL (B: (3OGQ GdKbGaI ddJUeje hGdEfJGL(B.s
(3HHdjhLQGajI (B: (3UaMI (B192.s
Keywords: (3GdGSJKeGQGJs -- (3bhGfjf hJTQjYGJs; (3GdbGfhf GdJLGQjs